Implementation of Simple Additive Weighting Method To Analyze The Selection of The Laptop - Luhut Frenando; Nury Handayani; Evi Niastuti; Susy Rosyida (Paradigma, 2023)
The existence of the laptop currently has been a basic need to help in completing work or daily activities. the many options of laptop types with different specifications are currently, creating some problems such as difficulty or confused when determining the laptop options to purchase. These problems are also found at the office of Satker PJN 1 Banten which is still done by considering only on laptop trends or only from specific advantages but not according to the existing needs and budget. The purpose of this research is to provide solutions to the problems by making a decision-making information system in analyzing the selection of the laptop at the office of Satker PJN 1 Banten. The proposed method is implementing the Simple Additive Weighting (SAW) method implemented by using a web-based application for the decision-making system in the selection of the laptop. The Simple Additive Weighting (SAW) method is a method used to produce the best alternative ranking value from some alternatives based on the weight of each criterion obtained from the result of the questionnaire data processing questionnaire. the results obtained from the selection of the laptop using the Simple Additive Weighting (SAW) method based on this web-based that can analyze the selection of the laptop objectively according to the ranking results of the calculations of the saw method, so the selection of the laptop is objective.